Separation of Mercury(II) from Aqueous Solution by Adsorption onto an Activated Carbon Prepared from - K. Kadirvelu; P. Kanmani; P. Senthilkumar; V. Subburam (Adsorption Science & Technology)
The adsorption of mercury(II) from aqueous solutions onto an activated carbon derived from Eichhornia crassipes (AEC) was investigated under varying conditions of agitation time, metal ion concentration, adsorbent dose and pH to assess the kinetic and equilibrium parameters. Adsorption equilibrium was attained in 200, 310, 360 and 360 min for 10, 20, 30 and 40 mg/l Hg(II) concentrations. The first- and second-order adsorption rate constants were calculated and the experimental equilibrium adsorption capacities (q e ) for different initial Hg(II) concentrations were reported. Adsorption was dependent on the solution pH, the Hg(II) concentration, the carbon concentration and the contact time. Both the Freundlich and Langmuir adsorption isotherm models fitted the experimental data well. The adsorption capacity was found to be 28.4 mg/g at pH 5 for a particle size of 125–180 μm. The adsorption capacity of the carbon produced met commercial conditions and was found to be superior to that of many other adsorbents. The percentage removal increased as the pH value of the solution was increased from 2 to 5 and then remained constant up to a pH value of 10. Desorption studies were performed with dilute hydrochloric acid and potassium iodide (KI) solutions.